Sintomatología depresiva en personas con perfeccionismo desadaptativo - Staub Gonzales, Mariana Camila (2022)
The prevalence of maladaptive perfectionism has increased in recent years, same as its influence on the development of depressive symptoms and its negative impact on the population. For this reason, the aim of this research is to determine the type of relationship between maladaptive perfectionism and depressive symptoms in adults. For this a review of the literature was conducted and inclusion and exclusion criteria were established for an adequate selection of articles, following the guidelines proposed by the PRISMA declaration (Page et al., 2021). The results showed that there is a significant relationship between maladaptive perfectionism and depressive symptoms, and also identified the presence of several mediating variables in this relationship. In addition, three of the studies revealed that maladaptive perfectionism functions as a predictor for depression. For future research, it is recommended that the influence of mediating variables be further analyzed in order to find ways to mitigate the effects of maladaptive perfectionism and depressive symptoms within de clinical context.